What are the differences in injury proportions between different populations of runners? A systematic review and meta-analysis - Kluitenberg, B.; van Middelkoop, M.; Diercks, R.; van der Worp, H. (Sports Medicine, 2015)
Background: Many runners suffer from injuries. No information on high-risk populations is available so far though.